The Implementation Of The Indonesia Ministry Of Industry Regulation In Supervising The Indonesia National Standard (SNI) Number 47 / M-DAG / PER / 7/2016 For Baby Cloting Of Small And Medium Entreprises’s - Kamal, Ubaidillah (Faculty of Law, Universitas Negeri Semarang, 2019)
This study aims to determine the factors that causes the spread of baby clothes which are not SNI labelled, in the city of Semarang and to find out the extent of the regulation?s implementation. The legal research that the writer use is qualitative research, with the type of juridical empirical research, in this method the primary data was obtained from the Department of Industry and Trade of Central Java Province and the Sekawan Putra Trade Business. Secondary data was obtained from library sources as well as from respondents namely baby clothing sellers and baby clothes consumers. The results of the study (1) internal factors that are not required to apply SNI on the use of baby products of IKM, the number of IKMs that still produce infant clothing that are not SNI labelled yet, the low awareness of consumers that is caused by less intensive socialization from the government, and external factors that come from dependence of business actors with laboratory tests, which makes it difficult for business actors to obtain SNI certificates. (2) No special supervision has been carried out as a follow up to the results of periodic supervision. Conclusions from this study (1) There are still many baby clothes of IKM products that are not SNI labelled yet (2) there is still a mismatch of the Minister of Trade Regulation of the Republic of Indonesia Number 47 / M-DAG / PER / 7/2016 carried out by the Department of Industry and Trade of Central Java Province. Suggestions from this research are for consumers to be more selective in choosing and buying baby clothes, for businesses to comply with SNI regulations for baby clothes, for the government to improve socialization to consumers and fostering business actors and conducting special supervision also increasing the frequency of monitoring.